Pt, Pd and Cu metal-amidine coordination - Taj, Muhammad Babar; Raheel, Ahmad; Tirmizi, Syed Ahmad; Sharif, Muhammad; Ahmad, Raja Hammad; Ali, Hapipah Mohd (Editura Academiei Romane, 2019)
Amidines, R’NH-C(R)=NR’, as for the isoelectronic carboxylic acids, form a variety of compounds incorporating transition metals from lower to higher oxidation states. Many studies reveal that Platinum, palladium and copper metals are very active in bonding with amidine moieties. The novelty of work presented here resides in an unified approach that deals with the interpretation of various types of bonding modes shown by amidine moieties and particularly the most remarkable achievements in the design and development of platinum, palladium and copper (II) complexes of substituted amidines. Special emphasis has been focused on the identification of structural relationships for the complexes formed. © 2019 Editura Academiei Romane. All rights reserved.